Community Development Program Through The Business Of Embroidery (A Study Of Mothers In Pakis Sub-District, Malang District) - Mahsuni, Abdul Wahid; Priyono, Achmad Agus; Kurniati, Kurniati (International Journal of Business, Law, and Education, 2024)
Development is a process carried out to help the community gain the power to make decisions and determine the actions to be taken. Including reducing the impact of personal and social barriers in taking action. One of the areas implementing community development programs is Pakis, East Java. Precisely located in Pakis District, Malang Regency. In Malang Regency itself, there is a government program, namely (Pakis Embroidery Palace). The program form of the Pakis Embroidery Palace activities is an embroidery exhibition that is held almost every year and is accompanied by an Embroidery Fashion Show which is attended by designers and MSME owners in Pakis so they can introduce their work to the public. The type of research used is a qualitative approach. Data collection techniques include gathering information through interviews and observations. From the results of focused observations regarding the development of micro-scale embroidery business actors in Pakis District, Malang Regency, it can be concluded that the development of micro-scale embroidery business actors in Pakis Regency is good. However, it still needs to be maximized. Most of the programs are dominated by women, but only a few are interested in taking embroidery training because today's young generation likes things that are instant or you could say they prefer to work in factories where the training is not difficult